2013
DOI: 10.1242/jeb.075739
|View full text |Cite
|
Sign up to set email alerts
|

Negative gravitactic behavior ofCaenorhabditis japonicadauer larvae

Abstract: SUMMARYGravity on Earth is a constant stimulus and many organisms are able to perceive and respond to it. However, there is no clear evidence that nematodes respond to gravity. In this study, we demonstrated negative gravitaxis in a nematode using dauer larvae (DL) of Caenorhabditis japonica, which form an association with their carrier insect Parastrachia japonensis. Caenorhabditis japonica DL demonstrating nictation, a typical host-finding behavior, had a negative gravitactic behavior, whereas non-nictating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 21 publications
0
14
4
Order By: Relevance
“…Gravity-sensing organs modulate a range of animal behaviors, including taxis (termed gravitaxis), posture orientation, body movements, and gaze stabilization [9][10][11]. Both positive and negative gravitaxis is widely observed in animals, including in aquatic zooplankton [12][13][14][15], amphibian, and teleost larvae [16,17], and in terrestrial invertebrates, such as Drosophila and Caenorhabditis japonica [18,19]. Despite the widespread occurrence of gravitaxis, the neural circuitry underlying these behaviors is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gravity-sensing organs modulate a range of animal behaviors, including taxis (termed gravitaxis), posture orientation, body movements, and gaze stabilization [9][10][11]. Both positive and negative gravitaxis is widely observed in animals, including in aquatic zooplankton [12][13][14][15], amphibian, and teleost larvae [16,17], and in terrestrial invertebrates, such as Drosophila and Caenorhabditis japonica [18,19]. Despite the widespread occurrence of gravitaxis, the neural circuitry underlying these behaviors is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the only comprehensive synaptic connectivity maps (i.e., connectomes) are from two invertebrates: the adult nematode Caenorhabditis elegans [20] and a larva of the tunicate Ciona intestinalis [21]. Although there are conflicting reports on whether C. elegans has a gravity response [18,22], Ciona larvae clearly do. The most commonly described gravitactic behavior in Ciona larvae is negative gravitaxis [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike arthropods, nematodes require high humidity for their movements; thus, using water agar in the assay arena improved nematode movement. In addition, the assay arena was positioned vertically because C. japonica DL have a tendency to move upward during host searching (Okumura et al, 2013c); this improved nematode locomotion and response to volatiles (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported that nictating C. japonica DL show a negative gravitactic behavior (Okumura et al, 2013c). The negative gravitactic behavior of DL appears to increase the opportunity to encounter its carrier insects wandering on the ground and could be useful for embarkation.…”
Section: Discussionmentioning
confidence: 99%
“…After 1 hr, we counted the number of nematodes that moved upward or downward from the inoculation point. The negative gravitaxis index was calculated as follows: (the number of nematodes moving in an upward direction -the number of nematodes moving in a downward direction)/total number of inoculated nematodes (Okumura et al, 2013c). Nematodes 1 cm from the central line were excluded from the dataset.…”
Section: Negative Gravitaxis Experimentsmentioning
confidence: 99%